PENGARUH AKUNTABILITAS, PENGALAMAN, DAN DUE PROFESSIONAL CARE AUDITOR TERHADAP KUALITAS AUDIT - Wardhani, Poppy Kusuma (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is conducted in 15 of 46 public accountant offices in Surabaya with a purpose to examine whether the auditorâs accountability, experience and due professional care have an influence simultaneously, partial, and dominant to the auditing quality. This research is conducted by applying questionnaire survey method. The population in this research is all auditors who work in the public accountant office in Surabaya. The simple random sampling is applied in this research and the criteria are the auditor who has at least one year working experience. The determination of the sample amount is based on the Gerson statement who stated that by using 50 â 100 people or more the sample can possibly represent the existing population. The data analysis is conducted by using the multiple regressions model. The result of the research indicates that accountability, experience and due professional care have an influence to the auditing quality simultaneously and partially. This research also proofs that due professional care is the dominant factor which has an influence to the auditing quality with percentage as much as 42.7%. Keywords: Accountability, Experience, Due Professional Care, Auditing Quality